2013
DOI: 10.1371/journal.pone.0071223
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index with Cause Specific Deaths in Chinese Elderly Hypertensive Patients: Minhang Community Study

Abstract: BackgroundMost studies have suggested that elevated body mass index (BMI) was associated with the risk of death from all cause and from specific causes. However, there was little evidence illustrating the effect of BMI on the mortality in elderly hypertensive patients in Chinese population.MethodsThe information of 10,957 hypertensive patients at baseline not less than 60 years were from Xinzhuang, a town in Minhang district of Shanghai, was extracted from the Electronic Health Record (EHR) system. All study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 28 publications
1
26
1
1
Order By: Relevance
“…Underweight was associated with increased mortality in previous studies [21][23]. In the present study, underweight was associated with all-cause, CVD, and expanded CVD mortality in the elderly.…”
Section: Discussionsupporting
confidence: 65%
“…Underweight was associated with increased mortality in previous studies [21][23]. In the present study, underweight was associated with all-cause, CVD, and expanded CVD mortality in the elderly.…”
Section: Discussionsupporting
confidence: 65%
“…In the Minhang Community Study 9 from China, Wang et al obtained information of 10 957 elderly hypertensive patients from an electronic health record system and followed them for a median of 3.7 years. They found that underweight, rather than overweight and obesity, was associated with all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…6 All major international guidelines recommend weight loss as part of the management of hypertension, but the BMI level associated with lowest mortality in these patients has not previously been well documented. 7 , 8 Wang et al 9 have reported that overweight and obesity were not associated with all-cause mortality in a group of Chinese elderly hypertensive patients. In one retrospective cohort study of adults with hypertension, a U-shaped relationship was observed between BMI and mortality.…”
Section: Introductionmentioning
confidence: 98%
“…The CDC recommends losing 5 to 10 percent of current body weight, which can decrease the blood pressure, blood sugar, and cholesterol (Centers for Disease Control and Prevention ,2018). Wang et al (2013) obtained information of 10 957 elderly hypertensive patients from an electronic health record system and followed them for a median of 3.7 years. They found that underweight, rather than overweight and obesity was associated with all-cause mortality.…”
Section: Figure 3: Bmi and Health Risks In Male And Female Populationmentioning
confidence: 99%